2010
DOI: 10.2353/ajpath.2010.090983
|View full text |Cite
|
Sign up to set email alerts
|

Parabiotic Heterogenetic Pairing of Abcc6−/−/Rag1−/− Mice and Their Wild-Type Counterparts Halts Ectopic Mineralization in a Murine Model of Pseudoxanthoma Elasticum

Abstract: Pseudoxanthoma elasticum (PXE), a pleiotropic heritable disorder, is characterized by ectopic mineralization of the connective tissues. This disease is caused by mutations in the ABCC6 gene, which is expressed primarily in the baso-lateral surface of hepatocytes, and Abcc6 ؊/؊ mice develop progressive mineralization mimicking human PXE. To investigate the hypothesis that PXE is a metabolic disorder, potentially caused by the absence of antimineralization factor(s) in circulation, we used parabiotic pairing, ie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…Transplanting skin from wild-type mice onto Abcc6 −/− animals resulted in mineralisation of the grafted tissue, whereas the reverse operation did not (Jiang et al, 2008). Surgical joining ( parabiosis) of Abcc6 −/− and wild-type mice halted ectopic mineralisation in the knockout animal (Jiang et al, 2010b), suggesting that the blood of wild-type mice carries an as-yet-unknown anti-mineralisation factor. One candidate for this factor is fetuin-A (alpha-2-HS-glycoprotein/Ahsg), a small liverderived protein which can inhibit hydroxyapatite precipitation (Schäfer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Transplanting skin from wild-type mice onto Abcc6 −/− animals resulted in mineralisation of the grafted tissue, whereas the reverse operation did not (Jiang et al, 2008). Surgical joining ( parabiosis) of Abcc6 −/− and wild-type mice halted ectopic mineralisation in the knockout animal (Jiang et al, 2010b), suggesting that the blood of wild-type mice carries an as-yet-unknown anti-mineralisation factor. One candidate for this factor is fetuin-A (alpha-2-HS-glycoprotein/Ahsg), a small liverderived protein which can inhibit hydroxyapatite precipitation (Schäfer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PXE is a metabolic disease caused by the absence of a factor, the presence of which depends on ABCC6 in the liver (17). Jiang and coworkers (14,18) previously showed that in an in vitro system using vascular smooth muscle cells, serum from Abcc6 +/+ mice inhibits mineralization to a greater extent than serum from Abcc6 −/− mice. We took a similar approach to test whether a mineralization-inhibiting factor is also present in medium from HEK293 cells overexpressing human ABCC6 (HEK293/hABCC6) or rat ABCC6 (HEK293/rABCC6).…”
Section: Abcc6-conditioned Medium Inhibits Mineralization Inmentioning
confidence: 99%
“…Abcc6 −/− muzzle skin that mineralizes in Abcc6 −/− mice does not mineralize when grafted onto WT mice, and muzzle skin of WT mice mineralizes only when grafted onto Abcc6 −/− mice (17). Moreover, surgically joining the systemic circulation of Abcc6 −/− mice with that of WT mice halts mineralization in Abcc6 −/− mice (18). Thus, PXE is caused not by a lack of functional ABCC6 in the affected tissues, but rather by the absence of a factor that is normally provided to the circulation by an ABCC6-dependent mechanism.…”
mentioning
confidence: 99%
“…Parabiotic surgery was performed as described previously [40][41][42]. A male Nes-Cre; R26-EYFP or Nes-Cre (control) mouse was surgically joined to a male ldlr -/ -mouse.…”
Section: Parabiosismentioning
confidence: 99%